Proceedings of the Thirty-Fifth Annual ACM Symposium on Theory of Computing 2003
DOI: 10.1145/780542.780595
|View full text |Cite
|
Sign up to set email alerts
|

Derandomizing polynomial identity tests means proving circuit lower bounds

Abstract: We show that derandomizing Polynomial Identity Testing is, essentially, equivalent to proving circuit lower bounds for NEXP. More precisely, we prove that if one can test in polynomial time (or, even, nondeterministic subexponential time, infinitely often) whether a given arithmetic circuit over integers computes an identically zero polynomial, then either (i) NEXP ⊂ P/poly or (ii) Permanent is not computable by polynomial-size arithmetic circuits. We also prove a (partial) converse: If Permanent requires supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
85
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 73 publications
(68 reference statements)
0
85
0
Order By: Relevance
“…In fact, an efficient deterministic blackbox identity test for arithmetic formulae of depth three or four already implies such lower bounds (Agrawal & Vinay 2008;Gupta et al 2013). Conversely, the well-known hardness versus randomness trade-offs imply that sufficiently strong Boolean circuit lower bounds yield efficient deterministic polynomial identity tests, and there are a couple of similar results starting from arithmetic circuit lower bounds as well (Dvir et al 2009;Kabanets & Impagliazzo 2004). cc (2015) PIT for multilinear bounded-read formulae 3…”
Section: Is There An Efficient Deterministic Identity Test For Arithmmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, an efficient deterministic blackbox identity test for arithmetic formulae of depth three or four already implies such lower bounds (Agrawal & Vinay 2008;Gupta et al 2013). Conversely, the well-known hardness versus randomness trade-offs imply that sufficiently strong Boolean circuit lower bounds yield efficient deterministic polynomial identity tests, and there are a couple of similar results starting from arithmetic circuit lower bounds as well (Dvir et al 2009;Kabanets & Impagliazzo 2004). cc (2015) PIT for multilinear bounded-read formulae 3…”
Section: Is There An Efficient Deterministic Identity Test For Arithmmentioning
confidence: 97%
“…Efficiently derandomizing identity testing implies Boolean or arithmetic formula/circuit lower bounds that have been elusive for half a century (Aaronson & van Melkebeek 2011;Kabanets & Impagliazzo 2004;Kinne et al 2012). In fact, an efficient deterministic blackbox identity test for arithmetic formulae of depth three or four already implies such lower bounds (Agrawal & Vinay 2008;Gupta et al 2013).…”
Section: Is There An Efficient Deterministic Identity Test For Arithmmentioning
confidence: 99%
“…The output of a PRG can thus be substituted for true randomness to obtain efficient simulations of BPP, by enumerating over all seeds. However, the existence of a uniform family of PRGs useful for derandomizing BPP implies circuit lower bounds that seem well beyond our current abilities to prove (and more recently, it has been shown that BPP = P itself implies circuit lower bounds [15]). Thus, in the absence of circuit lower bounds, the goal is to construct PRGs under a hardness assumption, and then we can hope for a family of constructions that represent a "best-possible" tradeoff between the hardness assumption required and the deterministic simulation implied by the PRG.…”
mentioning
confidence: 92%
“…However, obtaining deterministic polynomial time algorithms for PIT remained open since then. In 2004, Kabanets and Impagliazzo [11] showed that a deterministic polynomial time algorithm for PIT implies lower bounds (either NEXP ⊂ P/poly or permanent does not have polynomial size arithmetic circuits), thus making it one of the central problems in algebraic complexity. Following [11], intense efforts over the last decade have been directed towards de-randomizing PIT [21,25].…”
Section: Introductionmentioning
confidence: 99%